2012
DOI: 10.5812/hepatmon.830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multiplex Nested Polymerase Chain Reaction for Routine Hepatitis C Virus Genotyping in Egyptian Patients

Abstract: BackgroundAt least six HCV (hepatitis C virus) genotypes are unequally distributed worldwide. HCV genotyping guides the selection of treatment regimens and provides important epidemiological markers that enable the outbreak source to be traced and the spread of disease to be controlled. In Egypt, there is an increasing need for cost-effective, fast, and easily performable HCV genotyping assays.Recently, a multiplex PCR assay was developed to determine HCV genotypes. It employs genotype-specific primers, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…HCV genotyping was performed by a reverse hybridisation assay (Versant InnoLipa, HCV assays vs1 and vs2, Innogenetics, Zwijnaarde, Belgium and Siemens Diagnostics, Eschborn, Germany) for HCV genotypes 1, 2, and 3, or through Sanger sequencing of a 288 bp region in the NS5B gene for HCV genotype 4 samples [27] .…”
Section: Methodsmentioning
confidence: 99%
“…HCV genotyping was performed by a reverse hybridisation assay (Versant InnoLipa, HCV assays vs1 and vs2, Innogenetics, Zwijnaarde, Belgium and Siemens Diagnostics, Eschborn, Germany) for HCV genotypes 1, 2, and 3, or through Sanger sequencing of a 288 bp region in the NS5B gene for HCV genotype 4 samples [27] .…”
Section: Methodsmentioning
confidence: 99%
“…HCC is associated with a background of chronic and persistent infection of hepatitis B virus (HBV) or hepatitis C virus (HCV) (Caccamo et al, 2014). Data collected from the patients' medical files showed that they were HCV genotype 4, that was detected by RT-PCR, at our laboratory, at TBRI, according to the method documented by (Shemis et al, 2012). Biomarkers are beneficial in the detection of cancer at an early stage which is important since early detection has a direct effect on clinical outcomes and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…About 6% of Pakistani population is suffering from HCV infection. Therefore, epidemiological and genotyping studies are important to estimate its prevalence and to discover its improved and effective therapeutic treatments ( [17].…”
Section: Discussionmentioning
confidence: 99%